Effect of substrate orientation on strain relaxation mechanisms of InGaAs layer grown on vicinal GaAs substrates measured by in situ X-ray diffraction. (18th July 2017) - Suzuki, Hidetoshi; Sasaki, Takuo; Takahasi, Masamitu; Ohshita, Yoshio; Kojima, Nobuaki; Kamiya, Itaru; Fukuyama, Atsuhiko; Ikari, Tetsuo; Yamaguchi, Masafumi
Abstract: The effect of substrate orientation on strain relaxation mechanisms of an InGaAs layer grown on vicinal GaAs substrates was investigated by in situ X-ray diffraction (XRD). The crystallographic tilt and indium segregation in the InGaAs layer were altered depending on the miscut direction and angle. In the case of the substrate tilted 6° toward the [110] direction, one type of misfit dislocations was formed preferentially rather than other types, especially in the rapid relaxation phase. While in the case of the substrate tilted 6° toward the direction, no anisotropies during relaxation were observed. The present finding indicates that the appropriate use of vicinal substrates may lead to a novel method of improving the crystal quality of heterolayers.